2007
DOI: 10.1152/jn.00865.2007
|View full text |Cite
|
Sign up to set email alerts
|

Sleep/Wake Firing Patterns of Human Genioglossus Motor Units

Abstract: Although studies of the principal tongue protrudor muscle genioglossus (GG) suggest that whole muscle GG electromyographic (EMG) activities are preserved in nonrapid eye movement (NREM) sleep, it is unclear what influence sleep exerts on individual GG motor unit (MU) activities. We characterized the firing patterns of human GG MUs in wakefulness and NREM sleep with the aim of determining 1) whether the range of MU discharge patterns evident in wakefulness is preserved in sleep and 2) what effect the removal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 18 publications
4
44
0
Order By: Relevance
“…Average multiunit EMG activity was determined for the phasic (i.e., inspiratory) and tonic (i.e., expiratory) portions of each breath cycle. Because breathing frequencies varied between tasks, EMG measures at each electrode location were based on average EMG amplitude for 10 consecutive breaths (Mateika et al 1999;Eastwood et al 2003;Saboisky et al 2006Saboisky et al 2007Bailey et al 2007;Richardson and Bailey 2010). Because subtle differences in electrode impedance may alter the signal in terms of raw voltage, EMG values were normalized with regard to the regional maximal EMG activity (%maximum) and averaged across breaths.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Average multiunit EMG activity was determined for the phasic (i.e., inspiratory) and tonic (i.e., expiratory) portions of each breath cycle. Because breathing frequencies varied between tasks, EMG measures at each electrode location were based on average EMG amplitude for 10 consecutive breaths (Mateika et al 1999;Eastwood et al 2003;Saboisky et al 2006Saboisky et al 2007Bailey et al 2007;Richardson and Bailey 2010). Because subtle differences in electrode impedance may alter the signal in terms of raw voltage, EMG values were normalized with regard to the regional maximal EMG activity (%maximum) and averaged across breaths.…”
Section: Methodsmentioning
confidence: 99%
“…In view of the muscle's role as an airway dilator, the preponderance of research has focused on electromyographic (EMG) activity during sleep and wakefulness when subjects are in the supine or side-lying position (Eastwood et al 2003;Malhotra et al 2004;Fogel et al 2005;Bailey et al 2007;Eckert et al 2009;Wilkinson et al 2010;Jordan et al 2010;Richardson and Bailey 2010;Saboisky et al 2010;Laine and Bailey 2011;Trinder et al 2013). Numerous other studies have incorporated manipulations that impact upon respiratory-related GG activity, including head/body position (i.e., head up vs. head back; upright vs. supine) (Douglas et al 1993;Wasicko et al 1993;Ono et al 1996;Otsuka et al 2000;Tsuiki et al 2000;Williams et al 2000;Pae et al 2002Pae et al 2004Takahashi et al 2002;Walsh et al 2008), assessment of EMG activity in multiple muscle regions (Eastwood et al 2003;Wilkinson et al 2008Wilkinson et al 2010Nicholas et al 2010;Richardson and Bailey 2010;McSharry et al 2013;Trinder et al 2013), and in different tasks (i.e., rest breathing, voluntary hyperventilation, maximal inspiratory effort, or exercise) (Mezzanotte et al 1992;Williams et al 2000;Eastwood et al 2003;Walls et al 2013).…”
mentioning
confidence: 99%
“…These motor units are coordinated by complex premotor networks [29,44] that may be affected by anaesthesia [45]. The activity of different GG motor units changes differently during the transition from wakefulness to sleep [46][47][48]. Accordingly, the response of the GG to the transitions between sleep and wakefulness includes reorganisation of the pattern of motor unit activation within the muscle.…”
Section: Sleep-related Disorders Y Dotan Et Almentioning
confidence: 99%
“…We hypothesized that the different classes of motor units, previously described (38), would respond as a single population through increases in rate coding (increased firing frequency) and earlier activation of active units, together with recruitment of additional inspiratory phasic units under higher conditions of elevated CO 2 (10). In addition, because premotor inputs and their various thresholds for activation may alter the activation patterns (6,22), we hypothesized a marked reduction in the firing rates and derecruitment of inspiratory units with CPAP. Some of the results of these studies have been previously reported in the form of abstracts (37,42).…”
mentioning
confidence: 99%